Nursing care to patients with PiCCO monitoring - Ramona Rodríguez Flores; Alicia Oliva Cesar; Rafael Muriana Jiménez (Fundación para el Desarrollo de la Enfermería, 2009)
The monitoring of physiological parameters turns out to be indispensable to obtain a treatment directed therapeutic in critical patients.In the Units of Intensive care it is in the habit of being frequent to meet complex systems of monitoring homodynamic, since they are the Catheter of Pulmonary Artery (CAP) or of Swan-Ganz and the system of monitoring PiCCO (In English, Pulse-Induced Contour Cardiac Output), to measure the Cardiac Output for analysis of the curve of the arterial pulse.These systems are of necessary in patients with great instability homodynamic, septic shock, injury or pulmonary hurt and organic hurt.The lens of this work, it is to announce the system of monitoring PiCCO since it is a relatively new system and allows measuring parameters that do not decide with the catheter Swan-Ganz, besides other advantages. Also we have elaborated a plan of taken care of standard Nursing to patients with monitoring PiCCO.For his production we have based on a wide bibliographical review and expert consults professionals, as well as a deep navigation for Internet.